2017
DOI: 10.9734/arrb/2017/37324
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reproductive Traits of Different Androgenic Pepper Lines (Capsicum annuum L.)

Abstract: The biology of pepper growth and development is strongly dependent on complex influence of environmental abiotic factors as light, temperature, air humidity and soil moisture. The presence and length of different pepper phenophases are variety characteristics, which they expressed as result of the development in specific agroecological conditions. In this study the vegetation period as earliness indicator of seven androgenic pepper lines derived from 3 different sweet pepper varieties was studied during four y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Number of flowers and number of fertilized flowersArancon et al, 2004 found that the number of flowers of peppers grown in potting mixtures containing 10-80% vermicompost although greater did not differ significantly from those of peppers grown in MM360, whereas the pepper plants grown in the 80% vermicompost/20% MM360 had most flowers (8.6). In the Kapija pepper type, the average number of 7.56 flowers per plant for KK1 genotype was significantly lower than the flower number of KK2 (16.47 flowers) and control Kurtovska Kapija (14.43 flowers) however the mean number of fertilized flowers was 3.79 (KK2), 5.60 (KK1) and 5.21 (control Kurtovska Kapija)(Trajkova & Koleva Gudeva, 2017. In other research concerning bell pepper production in protected houses in India, the highest number of flowers (31.73) was obtained on black foil among other factors(Kumar & Verma, 2009) Tomar et al, 2018. found that tomato grown with bio-mulch produces the maximum number of flowers/inflorescence and number of inflorescence per plant.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Number of flowers and number of fertilized flowersArancon et al, 2004 found that the number of flowers of peppers grown in potting mixtures containing 10-80% vermicompost although greater did not differ significantly from those of peppers grown in MM360, whereas the pepper plants grown in the 80% vermicompost/20% MM360 had most flowers (8.6). In the Kapija pepper type, the average number of 7.56 flowers per plant for KK1 genotype was significantly lower than the flower number of KK2 (16.47 flowers) and control Kurtovska Kapija (14.43 flowers) however the mean number of fertilized flowers was 3.79 (KK2), 5.60 (KK1) and 5.21 (control Kurtovska Kapija)(Trajkova & Koleva Gudeva, 2017. In other research concerning bell pepper production in protected houses in India, the highest number of flowers (31.73) was obtained on black foil among other factors(Kumar & Verma, 2009) Tomar et al, 2018. found that tomato grown with bio-mulch produces the maximum number of flowers/inflorescence and number of inflorescence per plant.…”
mentioning
confidence: 79%
“…But in production, depending on the type of purpose the pepper is grown for, the term 'earliness' is used to describe the number of days from sprouting to the technological or botanical maturity (Bogevska et al, 2017). For crop improvement purposes selection for the traits, days to flowering, and days to fruiting will contribute to pepper earliness, thus it will increase the economic value of Kapija type genotypes (Trajkova & Koleva Gudeva, 2017). At an earlier time, Lamont, 1993 resumed that the use of plastic mulches shorten the vegetation period (7 to 14 days) and increased yields (two to three times) over bare soil in many vegetable crops.…”
Section: Introductionmentioning
confidence: 99%